Efficacy and Safety of Actinium-225 Prostate-Specific Membrane Antigen Radioligand Therapy in Metastatic Prostate Cancer: A Systematic Review and Metanalysis - Parida, Girish Kumar; Panda, Raj Abhisek; Bishnoi, Komal; Agrawal, Kanhaiyalal (Medical principles and practice, 2023)
Background: Actinium-225 (Ac-225) labelled PSMA RLT has been tested recently in metastatic castration-resistant prostate cancer (mCRPC), with encouraging results. Ac-225, being an alpha emitter, is expected to have higher efficacy and fewer side effects compared to the beta-emitters such as Lutetium-177. We have performed a meta-analysis to assess the therapeutic responses, survival effects, and significant side effects of Ac-225 PSMA RLT in patients with mCRPC. Methodology: Systematic literature search was carried out from five electronic databases PubMed/MEDLINE, SCOPUS, EMBASE, Web of Science, and Cochrane Library until March 2021. Eight studies were found to be eligible for this metanalysis. Results: Eight studies with 226 patients were analyzed in this metanalysis. 81% (95% CI 73–89) patients had a decline in PSA levels. 60% of the patients showed more than 50% PSA decline. Two studies assessed survival effects of radioligand naïve patients compared to patients who had received Lu-PSMA therapy previously and the pooled HR for radioligand naïve patients is 0.22. The most common toxicity reported was xerostomia in 167 patients out of 226 patients (73.9%, 95% CI 67.6–79.5%); however, most of them were confined to grade I and II levels. Other reported side effects include hematologic toxicity and nephrotoxicity. Conclusion: Ac-PSMA RLT is a safe and potentially effective treatment option for patients with mCRPC.